Impactos da expans\~ao do metrô de Fortaleza sobre o acesso a oportunidades de emprego, saúde e educaç\~ao - Carlos Kauê Vieira Braga; Diego Bogado Tomasiello; Daniel Herszenhut; Jo\~ao Lucas Albuquerque Oliveira; Rafael Henrique Moraes Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This study presents the results of an ex-ante assessment of the accessibility and equity impacts of a subway expansion in Fortaleza (Brazil). We analyze how the number of jobs, health facilities, and schools accessible by public transportation is expected to change with the implementation of a new subway line (Linha Leste) and the other changes planned in the Sustainable Accessibility Plan of Fortaleza (Pasfor). Our results indicate that investments in the rail system alone could increase the number of jobs, schools, and health services accessible by public transport by an average of 3.1% to 5.6%. However, the planned reduction of services in the bus network is expected to undermine the potential positive impact that would be obtained with the subway investments alone. With these service cuts, it is estimated that the number of opportunities accessible by public transport could drop by -7.4% to -8.1% on average compared to the 2019 baseline. As a rule, these accessibility reductions will be greater in middle- and low-income neighborhoods, indicating that the planned interventions on Fortaleza's public transportation network will have a regressive impact, increasing inequality of access to opportunities. The study brings important lessons about how transportation infrastructure expansion projects need to be planned in a coordinated manner with the day-to-day operation of public transportation systems to leverage the accessibility benefits of urban transportation policies.
Keywords: R40; R41; R48; R00; 330; public transport; accessibility; Fortaleza; impact assessment; transport inequalities; transport policy; equity